Development of a Cavity Disinfectant Containing Antibacterial Monomer MDPB. (December 2016) - Hirose, N.; Kitagawa, R.; Kitagawa, H.; Maezono, H.; Mine, A.; Hayashi, M.; Haapasalo, M.; Imazato, S.
An experimental cavity disinfectant (ACC) that is intended to be used for various direct and indirect restorations was prepared by adding an antibacterial monomer 12-methacryloyloxydodecylpyridinum bromide (MDPB) at 5% into 80% ethanol. The antibacterial effectiveness of ACC and its influences on the bonding abilities of resin cements were investigated. To examine the antibacterial activity of unpolymerized MDPB, the minimum inhibitory and bactericidal concentrations (MIC and MBC) were determined for Streptococcus mutans, Lactobacillus casei, Actinomyces naeslundii, Parvimonas micra, Enterococcus faecalis, Fusobacterium nucleatum, and Porphyromonas gingivalis . Antibacterial activities of ACC and the commercial cavity disinfectant containing 2% chlorhexidine and ethanol (CPS) were evaluated by agar disk diffusion tests through 7 bacterial species and by MIC and MBC measurement for S. mutans . The effects of ACC and CPS to kill bacteria in dentinal tubules were compared with an S. mutans –infected dentin model. Shear bond strength tests were used to examine the influences of ACC on the dentin-bonding abilities of a self-adhesive resin cement and a dual-cure resin cement used with a primer. Unpolymerized MDPB showed strong antibacterial activity against 7 oral bacteria. ACC produced inhibition zones against all bacterial species similar to CPS. For ACC and CPS, the MIC value for S. mutans was identical, and the MBC was similar with only a 1-step dilution difference (1:2). Treatment of infected dentin with ACC resulted in significantly greater bactericidal effects than CPS ( P < 0.05, analysis of variance and Tukey's honest significant difference test). ACC showed no negative influences on the bonding abilities to dentin for both resin cements, while CPS reduced the bond strength of the self-adhesive resin cement ( P < 0.05). This study clarified that the experimental cavity disinfectant containing 5% MDPB is more effective in vitro than the commercially available chlorhexidine solution to eradicate bacteria in dentin, without causing any adverse influences on the bonding abilities of resinous luting cements.